2019
DOI: 10.1016/j.jcrimjus.2019.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Where they live and go: Immigrant ethnic activity space and neighborhood crime in Southern California

Abstract: The current study advances the literature by simultaneously accounting for the geographic location of immigrant residences and the location of ethnic businesses, and considers their proximity to one another. We argue our alternative measure, which we term Immigrant Ethnic Activity Space (IEAS), more fully captures the ecology of immigrant communities. Using data from several sources to capture neighborhoods in the Southern California region, we constructed IEAS measures for the seven largest ethnic groups in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…The conceptual and perceived areas where individuals believe they share life, community, and cohesion with neighbors are vague, and this limitation has been controversial in the literature about neighborhood characteristics and crime (e.g., Kim & Hipp, 2020;Sampson, 2013). For example, Kim et al (2019) measured immigrants' daily activity patterns and identified new boundaries of neighborhoods for immigrants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The conceptual and perceived areas where individuals believe they share life, community, and cohesion with neighbors are vague, and this limitation has been controversial in the literature about neighborhood characteristics and crime (e.g., Kim & Hipp, 2020;Sampson, 2013). For example, Kim et al (2019) measured immigrants' daily activity patterns and identified new boundaries of neighborhoods for immigrants.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some assert that immigrant concentration in specific areas such as in neighborhoods marked by racial/ethnic segregation or disadvantaged areas could be linked to other disadvantages such as lack of employment opportunities, relatively lower wages for the same amount of work, low education attainment, language barriers, and more constricted patterns of structural integration (Alba & Nee, 1997;Feldmeyer, 2009;Kim et al, 2019;Sanders & Nee, 1987;Saporu et al, 2011). For example, the settling down of immigrants in disadvantaged areas has been associated with their being trapped in structural inequality.…”
Section: Crime-generating Effects Of Immigrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies find little evidence that areas with more immigrants are at heightened risk of neighborhood crime (Desmond & Kubrin 2009; Kim et al, 2018; Kubrin & Ousey 2009; Ousey & Kubrin 2014; Trager & Kubrin 2018). In fact, research typically shows that immigrant concentration has a null effect, or in some cases, a negative effect on neighborhood crime rates.…”
Section: Introductionmentioning
confidence: 99%
“…Mobility and its resulting associations between environmental exposures and health behaviours or outcomes may also differ by individual characteristics or by groups within the population. For instance, differences by socioeconomic status or age are infrequently considered (Fuller & Stanley, 2019; Kim et al., 2019; Portegijs et al., 2017; Smith et al., 2019). Exposure to fast‐food outlets often differs by socioeconomic status as these outlets more readily locate in more deprived areas (Black et al., 2014; Wiki et al., 2019).…”
Section: Introductionmentioning
confidence: 99%